“How can you kiss and touch this child and show affection towards her? What kind of woman are you?”: Provider perspectives on stigma towards native and ethnic minority street-connected youth in the Republic of Georgia - Sadzaglishvili, Shorena; Gotsiridze, Teona; Lekishvili, Ketevan; Flores, Rey; Hereth, Jane; Bouris, Alida (PloS one, 2023)
The Republic of Georgia has experienced a rapid growth in the number of youth working and/or living on the street (YWLS). Although research indicates that YWLS are highly stigmatized, few studies have examined perceptions of stigma among Georgian social service providers who serve YWLS. We conducted in-person in-depth interviews with key informants recruited from governmental institutions and social service organizations in Tbilisi and Rustavi, two large urban areas. A semi-structured interview guide was used to explore provider perspectives on the social contexts surrounding the delivery of services to YWLS. Trained coders conducted a thematic analysis of the data in Dedoose. Twenty-two providers (68% female; 32% male) were interviewed, representing diverse professional roles. Providers perceived that YWLS are subjected to strong public stigma and social exclusion at multiple social-ecological levels, with Roma and Kurdish-Azeri youth experiencing the strongest levels of social hostility, discrimination, and exclusion. Providers perceive that these dynamics prevent YWLS from developing trusting relationships with social service, health and educational institutions. Furthermore, we find that providers report encounters with courtesy stigma, i.e., stigma directed towards the people who serve or are associated with a stigmatized group, when working with YWLS, especially those from ethnic minority groups, which they characterize as a stressor. At the same time, we find that some providers reported negative stereotypes about ethnic minority YWLS. While campaigns have targeted public awareness on the plight of YWLS, study findings suggest that additional efforts are needed to address stigma directed towards YWLS, with a specific need to address stigma directed towards ethnic minority young people who work and/or live on the street.